Lessons from the Frontline: A Phenomenological Study into Faculty Members’ Experiences with Challenges of Remote Online Exams in Medical Sciences Universities - Mostafa Hadavinejad; Mahdieh Azin; Asieh Fatemidokht; Jalal Hassanshahi; Afsaneh Amiri Khorasani; Foad Iranmanesh (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2025)
Background: The rapid shift to remote online examinations in medical sciences universities during the COVID-19 pandemic posed unprecedented challenges for faculty worldwide. This study aimed to explore faculty experiences with the challenges of remote online examinations at Rafsanjan University of Medical Sciences, Iran.Methods: This qualitative inquiry utilized a phenomenological framework to conduct an in-depth exploration of faculty perspectives. Conducted at Rafsanjan University of Medical Sciences between September 2022 and February 2023, it involved 18 faculty members representing 15 various disciplines, with professional experience spanning four to thirty years. Purposeful sampling was implemented to ensure maximum diversity. Data were gathered through comprehensive, semi-structured interviews lasting between 60 to 90 minutes, conducted either face-to-face or through online platforms. All interviews were analyzed using the seven-step thematic content analysis approach developed by Diekelmann and colleagues, utilizing MAXQDA software.Results: The thematic analysis of the interviews yielded four primary dichotomous concepts, eight principal themes (components), and 24 sub-themes. The four dichotomies identified were: online examination versus in-person examination, fundamental ultimate action versus constrained immediate action, resources versus impediments, and alleviating stress versus exacerbating stress. The eight principal components delineated were: essential substitution, unavoidable invalidity, fundamental ultimate action, constrained immediate action, online examination resources, online examination impediments, alleviation of stress, and exacerbation of stress. Faculty views on online exams varied, with some seeing them as a valuable alternative and others concerned that they negatively impact education because of cheating and reduced feedback. Benefits mentioned included quick results and cost savings, while worries focused on technical issues and fairness.Discussion: Faculty experiences reveal a nuanced balance between the advantages and limitations of remote online examinations. While online assessments can improve logistical efficiency and reduce certain stressors, ongoing concerns about academic integrity, technical preparedness, and educational value persist. Addressing these issues requires investment in reliable infrastructure, comprehensive faculty training, and innovative valid assessment methods.